2022
DOI: 10.3390/jcm11164794
|View full text |Cite|
|
Sign up to set email alerts
|

Kynurenine Is the Main Metabolite of Tryptophan Degradation by Tryptophan 2,3-Dioxygenase in HepaRG Tumor Cells

Abstract: There are two main enzymes that convert tryptophan (Trp) to kynurenine (Kyn): tryptophan-2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO). Kyn accumulation can promote immunosuppression in certain cancers. In this study, we investigated Trp degradation to Kyn by IDO and TDO in primary human hepatocytes (PHH) and tumoral HepG2 cells. To quantify Trp-degradation and Kyn-accumulation, using reversed-phase high-pressure liquid chromatography, the levels of Trp and Kyn were determined in the culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…An estimated 90% of dietary Trp enters the kynurenine pathway, playing an important role in regulating homeostatic Trp concentrations, while also producing compounds capable of activating the AHR, including kynurenine, kynurenic acid, and xanthurenic acid. [9][10][11] A much smaller proportion of dietary Trp (~2%) enters the serotonin pathway, although these compounds are not known to directly interact with AHR and do not represent a current significant area of research. 12 Bacteria in the gut microbiome use an estimated 5% of Trp to produce indole-based derivatives.…”
Section: International Journal Of Tryptophan Researchmentioning
confidence: 99%
“…An estimated 90% of dietary Trp enters the kynurenine pathway, playing an important role in regulating homeostatic Trp concentrations, while also producing compounds capable of activating the AHR, including kynurenine, kynurenic acid, and xanthurenic acid. [9][10][11] A much smaller proportion of dietary Trp (~2%) enters the serotonin pathway, although these compounds are not known to directly interact with AHR and do not represent a current significant area of research. 12 Bacteria in the gut microbiome use an estimated 5% of Trp to produce indole-based derivatives.…”
Section: International Journal Of Tryptophan Researchmentioning
confidence: 99%
“…161 TDO has been revealed to be responsible for tryptophan degradation and kynurenine accumulation in liver cancer-associated hepatocytes. 162 Noteworthy, tryptophan metabolic reprogramming caused by CLD may aggravate the severity of COVID-19 patients. However, the participation of TDO and IDO in tryptophan metabolism during viral infection needs further investigation.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…In the MHV‐A95 infection mouse model, both TDO and IDO were significantly increased 161 . TDO has been revealed to be responsible for tryptophan degradation and kynurenine accumulation in liver cancer‐associated hepatocytes 162 . Noteworthy, tryptophan metabolic reprogramming caused by CLD may aggravate the severity of COVID‐19 patients.…”
Section: Pathological Mechanism Of Liver Injury Under Covid‐19mentioning
confidence: 99%
“…The utility of these newer generation TDO2 inhibitors for anti-cancer treatment remains to be determined. Studies using HepG2 liver cancer cells demonstrated that TDO2-inhibitors 680C91 or LM10 significantly reduced Trp degradation and that TDO2, but not IDO1, was the primary source of Kyn production in these cells ( 144 ). 680C91 has also been explored in other cancer types including melanoma ( 145 147 ), colon ( 147 ), leiomyomas ( 148 ), and gliomas ( 149 ).…”
Section: Targeting the Kynurenine Pathway For Anti-cancer Treatmentmentioning
confidence: 99%